Host–guest interaction and properties of cucurbit[8]uril with chloramphenicol - Zhang, Lin; Zheng, Jun; Luo, Guangyan; Li, Xiaoyue; Zhang, Yunqian; Tao, Zhu; Zhang, Qianjun (Beilstein Journal of Organic Chemistry, 2021)
The interaction between cucurbit[8]uril (Q[8]) and chloramphenicol (CPE) was investigated using single-crystal X-ray diffraction spectroscopy, isothermal titration calorimetry (ITC) and UV–vis, NMR and IR spectroscopy. The effects of Q[8] on the stability, in vitro release performance and antibacterial activity of CPE were also studied. The results showed that CPE and Q[8] formed a 1:1 inclusion complex (CPE@Q[8]) with an inclusion constant of 5.474 × 105 L/mol. The intervention of Q[8] did not affect the stability of CPE, but obviously reduced the release rate of CPE in artificial gastric and intestinal juice; Q[8] has a slow-release effect on CPE. The antibacterial results showed that the minimum inhibitory concentration (MIC) of CPE and CPE@Q[8] toward Escherichia coli (E. coli) was 1.5 × 10–3 and 1.0 × 10–3 mol/L, respectively, and toward Staphylococcus aureus (S. aureus), the MIC was 2.0 × 10–3 mol/L for both CPE and CPE@Q[8]. Therefore, Q[8] enhanced the inhibitory activity of CPE against E. coli.
Keywords: antibacterial activity; chloramphenicol; cucurbit[8]uril; host–guest interaction; in vitro cumulative release; stability

(untitled) - Lewis, E. A.; Adamek, T. L.; Vining, L. C.; White, R. L. (J. Nat. Prod., 2003)

(untitled) - Brooks, M. H.; Smith, R. L.; Macalady, D. L. (Appl. Environ. Microbiol., 1992)

(untitled) - Aiassa, V.; Zoppi, A.; Albesa, I.; Longhi, M. R. (Carbohydr. Polym., 2015)

(untitled) - Aiassa, V.; Zoppi, A.; Becerra, M. C.; Albesa, I.; Longhi, M. R. (Carbohydr. Polym., 2016)

(untitled) - Shi, J.-H.; Zhou, Y.-f. (Spectrochim. Acta, Part A, 2011)

(untitled) - Gannimani, R.; Ramesh, M.; Mtambo, S.; Pillay, K.; Soliman, M. E.; Govender, P. (J. Inorg. Biochem., 2016)

(untitled) - Ramos, A. I.; Braga, T. M.; Silva, P.; Fernandes, J. A.; Ribeiro-Claro, P.; Lopes, M. d. F. S.; Paz, F. A. A.; Braga, S. S. (CrystEngComm, 2013)

(untitled) - Freeman, W. A.; Mock, W. L.; Shih, N. Y. (J. Am. Chem. Soc., 1981)

(untitled) - Kim, K.; Selvapalam, N.; Oh, D. H. (J. Inclusion Phenom. Macrocyclic Chem., 2004)

(untitled) - Day, A.; Arnold, A. P.; Blanch, R. J.; Snushall, B. (J. Org. Chem., 2001)

(untitled) - Day, A. I.; Blanch, R. J.; Arnold, A. P.; Lorenzo, S.; Lewis, G. R.; Dance, I. (Angew. Chem., Int. Ed., 2002)

(untitled) - Liu, S.; Zavalij, P. Y.; Isaacs, L. (J. Am. Chem. Soc., 2005)

(untitled) - Cheng, X.-J.; Liang, L.-L.; Chen, K.; Ji, N.-N.; Xiao, X.; Zhang, J.-X.; Zhang, Y.-Q.; Xue, S.-F.; Zhu, Q.-J.; Ni, X.-L.; Tao, Z. (Angew. Chem., Int. Ed., 2013)

(untitled) - Flinn, A.; Hough, G. C.; Stoddart, J. F.; Williams, D. J. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Wu, F.; Wu, L.-H.; Xiao, X.; Zhang, Y.-Q.; Xue, S.-F.; Tao, Z.; Day, A. I. (J. Org. Chem., 2012)

(untitled) - Wu, L.-H.; Ni, X.-L.; Wu, F.; Zhang, Y.-Q.; Zhu, Q.-J.; Xue, S.-F.; Tao, Z. (J. Mol. Struct., 2009)

(untitled) - Jon, S. Y.; Selvapalam, N.; Oh, D. H.; Kang, J.-K.; Kim, S.-Y.; Jeon, Y. J.; Lee, J. W.; Kim, K. (J. Am. Chem. Soc., 2003)

(untitled) - Isobe, H.; Sato, S.; Nakamura, E. (Org. Lett., 2002)

(untitled) - Nau, W. M.; Florea, M.; Assaf, K. I. (Isr. J. Chem., 2011)

(untitled) - Whitesides, G. M.; Simanek, E. E.; Mathias, J. P.; Seto, C. T.; Chin, D.; Mammen, M.; Gordon, D. M. (Acc. Chem. Res., 1995)

(untitled) - Hunter, C. A.; Sanders, J. K. M. (J. Am. Chem. Soc., 1990)

(untitled) - Nishio, M.; Umezawa, Y.; Hirota, M.; Takeuchi, Y. (Tetrahedron, 1995)

(untitled) - Sun, J.; Guo, P.; Liu, M.; Li, H. (J. Mater. Chem. C, 2019)

(untitled) - Shi, L.; Liu, M.; Li, H. (CrystEngComm, 2020)

(untitled) - Ambler, J.; Brown, L.; Cockcroft, X.-L.; Grütter, M.; Hayler, J.; Janus, D.; Jones, D.; Kane, P.; Menear, K.; Priestle, J.; Smith, G.; Talbot, M.; et al. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Gui, X.; Liu, C.; Li, F.; Wang, J. (Ecotoxicol. Environ. Saf., 2020)

(untitled) - Axtmann, M.; Heier, M.; Hilali, W.; Weigand, B. (Int. J. Heat Mass Transfer, 2016)

(untitled) - Heo, J.; Kim, S.-Y.; Whang, D.; Kim, K. (Angew. Chem., Int. Ed., 1999)

(untitled) - Buschmann, H.-J.; Cleve, E.; Jansen, K.; Wego, A.; Schollmeyer, E. (J. Inclusion Phenom. Macrocyclic Chem., 2001)

(untitled) - Zhao, Y.; Bali, M. S.; Cullinane, C.; Day, A. I.; Collins, J. G. (Dalton Trans., 2009)

(untitled) - Xu, Z.; Lian, X.; Li, M.; Zhang, X.; Wang, Y.; Tao, Z.; Zhang, Q. (Chem. Res. Chin. Univ., 2017)

(untitled) - Xie, J.; Zeng, Z.; Tao, Z.; Zhang, Q. (Chem. Res. Chin. Univ., 2020)

(untitled) - Zeng, Z.; Xie, J.; Luo, G.; Tao, Z.; Zhang, Q. (Beilstein J. Org. Chem., 2020)

(untitled) - Zhang, X.; Xie, J.; Xu, Z.; Tao, Z.; Zhang, Q. (Beilstein J. Org. Chem., 2020)